(untitled) - Thái, Nguyễn Tường Vi (Cần Thơ, 2013)
The current research is aimed at examing the effect of implementing CLIL on EFL learners' writing performance. It also seeks to explore which aspect of writing performance is most influenced by CLIL method.
Keywords: English language,Phương pháp giảng dạy tiếng Anh; Study and teaching